Exploring The Innovativeness Of The South Caucasus Economies: Main Trends And Factors - Ibrahim Niftiyev; Nargiz Yagublu; Narmin Akbarli (SocioEconomic Challenges, 2021)
The main purpose of the present research is to establish an exploratory picture of innovativeness in Armenia, Azerbaijan, and Georgia. The main trends and key determinants of innovativeness in the South Caucasus have rarely been investigated in mainstream economic research. However, the South Caucasus is a rapidly developing post-Soviet region, and it is geographically strategic for several key players in the global economy, including China and the European Union (EU). In fact, the role of the South Caucasus in international economic agreements is growing due to increased partnerships between Eastern and Western countries. Thus, the region’s current and future innovativeness will determine its integration into global value chains (GVCs). This study employs figure analysis to examine and compare the innovativeness of individual countries and the region as a whole against relevant economic and institutional indicators discussed in the literature. Using scatter plots, a polynomial trendline approach allowed the data to be divided into more meaningful periods of analysis to better understand peaks and dips in national innovativeness in association with selected economic and institutional indicators in the South Caucasus. Overall, the results show that economic growth and economic freedom play an important role in innovativeness in the South Caucasus, while institutional factors present more of a mixed picture. More specifically, the region’s overall innovativeness was positively correlated with rule of law and property rights to a certain extent, but this association was not consistent. In addition, Armenia and Georgia experienced higher growth in national innovativeness between 2011 and 2020, while this growth was weaker in Azerbaijan. This paper’s results may help the South Caucasus countries conceptualize their innovativeness in terms of the region’s overall innovativeness and key economic and institutional variables. Moreover, more sophisticated quantitative techniques and econometric models may be applied in future research.